Human Fitrah and his potentialities towards virtue and morality - Ali, Md. Yousuf (Zes Rokman Resources, 2016)
Human fitrah is an innate spiritual quality of man and his potentialities are as means for improving his/her good moral quality. In Islam, every new-born baby is born in a state of fitrah. Then his parents make him a Jew, a Christian or a Muslim. In contemporary time, a westernized man is greatly influenced by the anti-religious trends within secular modernity, which is against his/her fitrah. It is necessary for man to understand his/her fitrah, to realize the role of his/her potentialities in order to improve high good moral quality and to establish value-based human society. The paper therefore examines man’s fitrah and the role of his potentialities and analyzes these within the purview of contemporary Islamic thought which is based on the textual arguments of the Qur’Én and Sunnah. The paper concludes that many Muslim scholars have viewed human fitrah and his potentialities as means for developing high good moral quality.